Hans Joas' Creativity Theory of Action and its Implications for Reconstructive Anarchism - Torriani, Tristan Guillermo (Cognitio-Estudos: revista eletrônica de filosofia, 2013)
Hans Joas has recently developed a Pragmatist theory of action that posits creativity (understood as an innovative problem-solving solution that alternates between habit and adjustment) as a precondition for all human behavior. His aim is to provide a fundamental action-theoretical alternative that departs from the assumptions of rational action theory, be it teleological (Utilitarian) or normative. While his proposal has been well received, several objections have been raised against it. After presenting his main theses and the major criticisms made to his theory, I examine its implications for a reconstruction of Anarchism. Creativity in the Anarchist tradition is very central as form of human development, both on the individual and collective levels, but Joas' concepts of "situated creativity" and "primary sociality" requires a revision of classical Anarchist demands for individualism and equality. I nevertheless show that Joas' Pragmatism and Bakunin's Anarchism are compatible to a considerable degree.